Lung to Finger Circulation Time in Sleep Study and Coronary Artery Calcification: The Multi-Ethnic Study of Atherosclerosis [Brief Communication] - Kwon, Younghoon (Sleep Med, 2020)
Lung to finger circulation time (LFCT) measured from sleep studies may represent a novel physiologic marker for cardiovascular risk in patients with sleep disordered breathing (SDB). We hypothesized that sleep study-derived LFCT would improve risk classification of markers of subclinical cardiovascular disease. We included participants in the Multi-Ethnic Study of Atherosclerosis (MESA) Sleep cohort with moderate-severe SDB (apnea hypopnea index [AHI] ≥ 15/hr) (N=598). Those with average LFCT above the median (19.4 sec) (vs. shorter LFCT) tended to be older, more obese and male. In multivariable analysis, no significant associations were found between average LFCT and subclinical cardiovascular markers including coronary artery calcium, carotid intima-media thickness or left ventricular hypertrophy. However, there was modest improvement in risk classification of coronary artery calcification as compared with AHI alone when average LFCT was added to AHI (C statistics 0.53 vs. 0.62, p=0.0066). In conclusion, LFCT may be a useful addition to conventional SDB metrics to improve cardiovascular risk assessment.